Recent Changes in Wolf Habitat Occupancy and Feeding Habits in Italy: Implications for Conservation and Reducing Conflict with Humans - Meriggi, A; Torretta, E; Dondina, O (Springer International Publishing, 2020)
Despite the generally positive trend of European populations, the wolf (Canis lupus) is still today a challenging species to conserve, particularly in the most anthropogenic southern European countries, because of its conflict with humans. In this chapter we summarize the dynamics of wolf distribution in Italy, one of the most densely populated European countries, over the last 50 years. We track changes in the wolf’s diet by comparing its change in Italy with other countries, with the aim of understanding how these changes may have affected the evolution of the human-predator conflict in Italy. In particular, we summarize the results of studies both in Italy and in other European countries to clarify the true impact of wolf predation on both livestock and wild ungulates, which represent the two main causes of predator-human conflict. In order to provide specific insight about the past and the current distribution and feeding habits of the wolf in Italy, and to take stock of the conflict between wolves and humans, we present three case studies. All were carried out over recent decades in northern Italy, i.e. in the area where wolf packs, and particularly their ability to produce dispersing individuals, could affect the future of the entire Italian population. Finally, we consider how to mitigate wolf-human conflict and suggest effective management of wolf populations.